2019
DOI: 10.1038/s41598-018-37984-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multiple Magnetic Resonance Imaging Sequences Provides Independent Reproducible Radiomics Features

Abstract: To evaluate the relative contribution of different Magnetic Resonance Imaging (MRI) sequences for the extraction of radiomics features in a cohort of patients with lacrimal gland tumors. This prospective study was approved by the Institutional Review Board and signed informed consent was obtained from all participants. From December 2015 to April 2017, 37 patients with lacrimal gland lesions underwent MRI before surgery, including axial T1-WI, axial Diffusion-WI, coronal DIXON-T2-WI and coronal post-contrast D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
(46 reference statements)
0
27
0
Order By: Relevance
“…3, S1 and S2), a number of bins equal to 32 seems to be a good compromise for brain MR analysis after Z-Score normalization, as it leads to the most informative radiomics signatures for both sequences, with acceptable calculation times. Preliminary feature selection based on robustness is widely used in radiomics 45,46 . In the present study, no improvements in classification performances were observed using feature selection ( Figure S2, Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…3, S1 and S2), a number of bins equal to 32 seems to be a good compromise for brain MR analysis after Z-Score normalization, as it leads to the most informative radiomics signatures for both sequences, with acceptable calculation times. Preliminary feature selection based on robustness is widely used in radiomics 45,46 . In the present study, no improvements in classification performances were observed using feature selection ( Figure S2, Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics features, reliability and reproducibility can be affected by various aspects of radiomics processing (e.g., image acquisition parameters and protocols, image preprocessing algorithms, tumor segmentation, and software used for processing and feature extractions). Major of radiomics studies by concerning a different aspect of radiomics reproducibility and repeatability issue was done in computed tomography (CT) and PET modalities for limited cancer types, and a few studies have been reported in MRI …”
Section: Introductionmentioning
confidence: 99%
“…Typically, robust biomarkers are derived from large heterogeneous datasets with a methodical testing process and external validation. Currently, literature has shown that radiomic features can be influenced by many parameters such as scanning equipment [187,188], image pre-processing [189], acquisition protocols [190,191], image reconstruction algorithms [13,192,193], and delineation [194,195] among others. These changes can subsequently impact the radiomic predictive models.…”
Section: Reproducibility Of Radiomic Featuresmentioning
confidence: 99%